Imperfect memory and the preference for increasing payments - John Smith (Rutgers University, Department of Economics, 2008)
In this paper we show how imperfect memory can imply a preference for increasing payments. We model an agent making a decision regarding effort in two periods where the cost of effort is imperfectly known. Before making the first decision, the agent receives a signal related to the cost of effort, which is subsequently forgotten. Before the second decision, the agent makes an inference regarding the content of this signal based on the publicly available information: the action taken and the wage paid. A preference for increasing payments naturally emerges from our model. With the auxiliary assumption that obtaining wage income requires an unknown cost of effort and obtaining rental income requires a known, zero cost of effort, our results provide an explanation for the experimental findings of Loewenstein and Sicherman (1991). These authors find evidence of a stronger preference for increasing income from wages rather than income from rent. Additionally, our model makes the novel prediction that this preference for increasing payments will only occur when the contracts are neither very likely nor very unlikely to cover the cost of effort.
Keywords: D8; 330; imperfect recall; self-perception theory; sequences of payments; Entscheidungstheorie; Unvollkommene Information; Kognition; Theorie